A Simplified Guide for Arranging 30ÃƒÂ¢Ã¢â‚¬â€Ã‚Â¦ Pilkington Turner Posterior Denture Teeth in a Balanced Occlusion - Dennis Nilsson, DDS, MS1 and Thomas Meng, DDS2 (Journal of Prosthodontics, 2007)
A simple technique is presented for achieving balanced occlusion when setting 30ÃƒÂ¢Ã¢â‚¬â€Ã‚Â¦ Pilkington-Turner teeth